The Implementation of Smart Application System for Early Detection of Stunting as a Solution to Nutritional Problems Based on Anthropometry Standards - Muflihatin, Indah; Wicaksono, Andri Permana; Mudiono, Demiawan Rachmatta Putro; Arum, Puspito; Nurmawati, Ida; Muna, Niyalatul (International Journal of Health and Information System, 2024)
Stunting is a nutritional status determined by the PB/U or TB/U index. These measurements fall within the threshold (Z-Score) <-2 SD to -3 SD (short/stunted) and <-3 SD (highly short). Per the 2024 target established by the president, the frequency of stunting can be reduced to 14%. It has been demonstrated that there are still dietary disorders, particularly in the vulnerable age group, namely toddlers in Kemuning Lor Village. In 2018, there were still 33 toddlers with nutritional status disorders, including 24 toddlers (19.7%) with overnutrition, 5 toddlers (4.1%) with undernutrition, and 4 toddlers (3.2%) with malnutrition. Smart Systems is a subfield of Computer Science that focuses on developing competent methods inspired by natural events to address various complicated problems in the real world, including the health realm; early detection of stunting. This study aimed to develop an early detection method for nutritional status and stunting based on anthropometric standards in toddlers in Kemuning Lor Village, which is anticipated to aid cadres or the community in overcoming nutritional status and stunting in toddlers.